The Attributes of The Corporate Governance to The Quality of Corporate Social Responsibility Disclosure - Ikbar Pratama; Khalik Pratama; Diny Atrizka; Mohd Idris Dalimunthe (Postgraduate Program Merdeka University, 2024)
This study aims to explore the relationship between corporate governance attributes (such as political connections, proportion of women, multiethnicity, family ownership, and board composition) with CSRD quality. The independent variables for this study are gathered from the 2023 annual reports of each listed company on the IDX. Meanwhile, the dependent variable, CSRD quality, is summarized from the environmental and social disclosures present in these annual reports. The disclosed information is then converted into a percentage to represent the score of CSR disclosure quality. The research sample was 460 companies listed on the Indonesia Stock Exchange (IDX) in 2023. The association between corporate governance attributes and CSRD quality examined using multiple regression. The outcomes of the multiple regression analysis reveal that the political connection of the board of commissioners (PCOBC) and the composition of the board of directors (TCOBD) significantly impact CSRD quality among the 460 Indonesian publicly listed companies in the year 2023.DOI: https://doi.org/10.26905/afr.v7i2.12668